2019
DOI: 10.7759/cureus.5660
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital Outcomes and Characteristics of Heart Failure in Sickle Cell Disease

Abstract: Sickle cell disease (SCD) predominantly affects African-Americans (AAs) in the United States (US). Due to increasing life expectancy in developed countries, SCD-associated cardiomyopathy is typically seen in adults. The aim of this study was to distinguish hospitalization for this phenotype from traditional heart failure (HF) in AAs. We used the National Inpatient Sample (NIS) database to identify HF hospitalizations in AAs between 2005 and 2014 and stratified them according to SCD status. We compared the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the recent study, the pattern of heart failure in Afro-Americans (AA) with SCD versus heart failure in AA without SCD was studied with the help of the National Inpatient Sample Database (NIS), which represents more than 97% of the US population. While it is known that heart failure occurs at an earlier age in African-American (AA), but this study observed that the chances of getting heart failure increase even further in AA patients with SCD [1].…”
Section: Pathophysiology Of Scd-related Cardiomyopathy and Its Complimentioning
confidence: 67%
See 3 more Smart Citations
“…In the recent study, the pattern of heart failure in Afro-Americans (AA) with SCD versus heart failure in AA without SCD was studied with the help of the National Inpatient Sample Database (NIS), which represents more than 97% of the US population. While it is known that heart failure occurs at an earlier age in African-American (AA), but this study observed that the chances of getting heart failure increase even further in AA patients with SCD [1].…”
Section: Pathophysiology Of Scd-related Cardiomyopathy and Its Complimentioning
confidence: 67%
“…SCD, which originated from Sub-Saharan Africa, Southeast Asia and India, has been known to be the most common inherited hemoglobinopathy worldwide due to increasing migration in the modern world. Prolonged exposure to high cardiac output state from chronic anemia in SCD leads to significant dilatation of LV which, over time, adapts to increased wall stress by developing eccentric LV hypertrophy, as shown in Figure 1 [1,7,8]. Myocardial remodeling can be well tolerated for a long time; however, myocardial damage can occur from chronic volume overload leading to exercise intolerance and heart failure.…”
Section: Pathophysiology Of Scd-related Cardiomyopathy and Its Complimentioning
confidence: 99%
See 2 more Smart Citations